The influence of alcohol (0.5‰) on the control and manoeuvring level of driving behaviour, finding measures to assess driving impairment: A simulator study - van Dijken, J.H.; Veldstra, J.L.; van de Loo, A.J.A.E.; Verster, J.C.; van der Sluiszen, N.N.J.J.M.; Vermeeren, A.; Ramaekers, J.G.; Brookhuis, K.A.; de Waard, D. (Transportation research. Part F, Traffic psychology and behaviour, 2020)
•Variation in speed and lateral position are suitable to assess driving impairment.•Adopted distance to other vehicles measures higher level driving impairment.•Reaction time to a traffic light is sensitive to higher level driving impairment.•Measures that allow freedom of choice need more in depth research. The influence of psychoactive substances on driving performance and traffic safety has been extensively studied. Research on the influence of alcohol at the control level of behaviour (i.e. automated processes) has been well established and has shown that the ability to operate a vehicle decreases with rising alcohol levels. However, results one level higher at the manoeuvring level (i.e. conscious processes), are inconsistent. The current study aimed to replicate findings on the influence of alcohol on the control level of behaviour and investigate effects on the manoeuvring level in order to find suitable measures to assess driving impairment. The study was double-blind, placebo-controlled with a counterbalanced treatment order and a two-way crossover design. Thirty participants performed tasks in a driving simulator under the influence of alcohol (0.5‰) and a placebo. In the driving tasks the control level of behaviour (swerving, average speed, and speed variation) was investigated, as well as the manoeuvring level of behaviour (distance to other traffic during an overtaking manoeuvre, reaction time to a traffic light turning amber, and response to a suddenly merging car). As expected, alcohol affected the control level of behaviour negatively. Participants swerved more and showed more speed variation after alcohol intake. The manoeuvring level of driving behaviour was also affected by alcohol. The distance to other drivers during an overtaking manoeuvre was smaller under the influence of alcohol. Results on reaction time were however less straightforward. Reaction time increased significantly under the influence of alcohol when reacting to a traffic light but not in reaction to a car unexpectedly merging into traffic. When analysing behaviour in reaction to these different events in more detail it became clear that they were responded to in varying manners, making it difficult to find an average impairment measure. The deteriorating effect of alcohol at the control level of driving behaviour was replicated, confirming the suitability of the standard deviation of lateral position and the variation in speed as measures of impairment. At the manoeuvring level, the kept distance to the leading car during an overtaking manoeuvre appeared to be a suitable measure to assess impairment as well as reaction time to a traffic light. The current study also confirms the difficulties in evaluating complex driving behaviour and the need for more research on this subject.